Mechanical circulatory support in acute myocardial infarction and cardiogenic shock: Challenges and importance of randomized control trials. Issue 7 (7th March 2021) - Basir, Mir B.; Pinto, Duane S.; Ziaeian, Boback; Khandelwal, Akshay; Cowger, Jennifer; Suh, William; Althouse, Andrew
Abstract: Background: Acute myocardial infarction (AMI) complicated by cardiogenic shock (CS) is associated with significant morbidity and mortality. Methods: We provide an overview of previously conducted studies on the use of mechanical circulatory support (MCS) devices in the treatment of AMI‐CS and difficulties which may be encountered in conducting such trials in the United States. Results: Well powered randomized control trials are difficult to conduct in a critically ill patient population due to physician preferences, perceived lack of equipoise and challenges obtaining informed consent. Conclusions: With growth in utilization of MCS devices in patients with AMI‐CS, efforts to perform well‐powered, randomized control trials must be undertaken.